Interpellations from Functional Diversity. the (Un) Fair Measure of Ability in Chile - Valenzuela-Rabi, A (CENTRO ESPANOL DOCUMENTACION DISCAPACIDAD-CEDD, 2015)
This article is framed in the context of the doctoral thesis "Public policies of inclusive education: logical mechanisms and settings. The case of Chile and USA". It approaches the effectiveness of education inclusion policies, from the viewpoint of sociology of the individual and adopting a realist research approach. This approach is adopted in order to account for the nature of social change proposed and to describe how resources are linked in furtherance of the objective and the ways in which they are offered for interpretation by the subjects of politics. Evidence suggests that the graduates call inclusion into question, whether by the means of identification used to access, the social treatment to be overcome in order to remain once included or the assessment of personal effort that is made to meet diverse school requirements imposed by the educational system.